Characteristics and Outcome of Babies with Antenatal Renal Pelvis Dilatation (RPD) - Ayesha Siddique, Rafia Gul, Zahid Anwar, Nida Siddique, Faiza Yasin, Zunaira Naeem Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Antenatal renal pelvis dilatation (RPD) is the most common congenital renal anomaly detected on antenatal ultrasound. The present study was planned to determine the characteristics and outcome of neonates with antenatal renal pelvis dilatation. Patients and Methods: A prospective, observational, non-interventional study was conducted in Fatima Memorial Hospital over a period of 12 months from April 2021 to March 2022. This study included 130 kidneys of 91 neonates >28 weeks of gestation with antenatally diagnosed isolated renal pelvis dilatation. Postnatal ultrasound was performed at 24-72 hours of life. Cases those resolved spontaneously were labelled as Physiological RPD (Transient RPD) , while all others were labelled as Pathological RPD (Persistent RPD).Descriptive statistics and tests of significance were calculated for all variables. Univariate analysis was performed to compare all possible risk factors for postnatal transient vs. persistent RPD of any grade. Correlation coefficients were calculated between risk factors with pathological RPD. Results: Every 4th neonate of antenatally diagnosed RPD had persistent RPD (p<0.05). Only 5% of neonates showed a severe variety of persistent RPD. Statistically significant risk factors associated with pathological RPD were maternal anemia, oligohydramnios, diabetes mellitus, gestation age < 37 weeks, birth weight <3 kg, antibiotics administration, admission in intensive care unit, urinary tract infections, oliguria, high BUN and creatinine, posterior urethral valve, vesicoureteral reflux, neurogenic bladder and other urinary tract malformations (P<0.05). Persistent RPD had a strong positive direct correlation with the severity of antenatally diagnosed RPD, a moderate positive correlation of persistent RPD was seen with maternal anemia, oligohydramnios, high serum creatinine, PUV, and PUJ. Hence the study will help us in formulating management and follow up plan of our newborns with antenatal RPD. Conclusion: About 71% of neonates with antenatally diagnosed RPD undergo spontaneous resolution. Severe antenatally diagnosed RPD persisted in neonatal life and persistent RPD has a strong correlation with the severity of renal pelvis dilatation. Keywords: Ultrasonography, Renal Pelvis Dilatation (RPD), Antenatal, Postnatal, PUJ, Urinary tract malformation, neonatal kidney.